CEO compensation, corporate social responsibility (CSR) and firm performance: evidence from China - Miao Wenhao; Junainah Jaidi; Rosle Mohidin (Universiti Malaysia Sabah, 2020)
This paper investigated the moderating effect of Corporate Social Responsibility (CSR) on the relationship between CEO compensation and firm performance on the Chinese capital market. This paper applied a panel data regression technique using data composition represented by SSE180 index for a period spanning from 2010 until 2019. A total of 86 representative large listed firms was employed in this paper for the period of 10 years with a total of 860 firm-year observation. The empirical results showed that both CEO compensation and CSR have a significant positive relationship with firm performance. More importantly, this paper found that the level of CSR moderates (reduces) the relationship between CEO compensation and firm performance. Therefore, the results implied that although CSR is a useful business strategy, it still has a lot of room for improvement.